Tenacificação de polímeros frágeis com a inserção de uma segunda fase polimérica dotada de memória de forma - Giuliano Siniscalchi Martins (2015)
We have studied an alternative to improve the mechanical properties of brittle polymers with the use of a shape memory polymer as a second phase. The blends were produced using polystyrene (PS, brittle matrix) and shape memory polyurethane (PU/MF, second phase). Samples PU/MF were synthesized in aqueous dispersion (PU/MFAGUA), dissolved in THF (PU/MFTHF) and with the incorporation of poly(styrene-co-maleic anhydride) (PU/MFSMA). The properties of the polyurethanes showed a strong relationship with the crystalline fraction of the soft domains. The PU/MFAGUA and the PU/MFTHF exhibited brittle behavior when they were crystallized and ductile behavior after heat treatment for controlling crystallinity. A study of the synthesis medium with the PU/MFAGUA and PU/MFTHF showed that, by replacing the water for THF in the synthesis, a reduction of the crystalline fraction of the polymer was observed. The presence of poly(styrene-co-maleic anhydride) in PU reduced the crystalline fraction and led to a ductile behavior even without heat treatments. The blends were obtained by thermomechanical mixing with / without addition of poly(styrene-co-maleic anhydride). The obtained blend exhibited a high phase separation caused by immiscibility of the blend components. SEM images showed phase morphology formed by an interconnected matrix of PS (structural component) containing areas of PU whose geometry and dimensions vary with concentration. The mechanical tests showed an increase in impact strength with heat treatment suggesting that shape memory effect was activated. The addition of a second phase that have shape memory is presented as an alternative for improving the mechanical properties of brittle polymers.